PENGEMBANGAN MEDIA TREASURE OF SCIENCE BERBASIS KEARIFAN LOKAL REMBANG DALAM PEMBELAJARAN IPA TERPADU - Ni'mah, Fadlilatun; Wulandari, Ana Yuniasti Retno; Tamam, Badrud; Putera, Dwi Bagus Rendy Astid; Rakhmawan, Aditya (Natural Science Education Research, 2023)
This study aims to analyze (1) the feasibility of Rembang local wisdom-based treasure of science media in integrated science, and (2) studend responses to Rembang local wisdom-based treasure of science media in integrated science. This study uses the Borg and Gall research model which uses 5 development steps, namely research and information collecting, planning, development of preliminary form of product, preliminary field testing, and main product revision. Trial data collection techniques used are interview techniques, questionnarires and documentation, while the data analysis of student responses. The results showed that the terasure of science media based on Rembangblocal wisdom in integrated science learning that was developed was categorized as very feasible to use (valid) as a learning medium fo SMP/MTs students with an average material feasibility assessment of 93,33%, media feasibility of 90,83% and student responses of 87%.